Analysis Of The Staggered Crossbeam Of Pier Designed Based On Deep Beam Design Concept - Ko, Jiunn Xuan (Universiti Sains Malaysia, 2021)
The deep beam concept has different load transferring behaviour from the simple beam concept. Deep beam develops diagonal tension zone extends from loading point to support point, causing the shear cracking and leading to failure of the structure. The staggered crossbeam in the pier in an existing completed project had occurred the deep shear cracking due to lack of consideration of deep beam concept during the design stage, resulting in the heavy and complicated remedial works. Therefore, this study focuses on analysing the staggered crossbeam of pier designed based on established design philosophy. In this study, two staggered crossbeams of the pier with similar geometrical dimensions were designed based on the STM and simple beam concept, respectively. The reinforcements provided by these two methods were compared and evaluated. The result showed that the reinforcement provided by the STM is more than that designed based on simple beam concept. Moreover, the finite element analysis was conducted for staggered crossbeam pier with varied crossbeam elevation differences to assess the behaviour of reinforced concrete and the adequacy of reinforcement provided when subjected to concentrated vertical loads. The models were divided into five categories with a different elevation of right crossbeam and provided six reinforcement groups for each model. The models were analysed with ABAQUS finite element analysis software. The analysis result indicated that the adequacy of reinforcement for staggered crossbeam of the pier is reduced when the variation of crossbeam elevation increases. The adequacy of reinforcement for the staggered crossbeam of the pier was obtained based on the model with the least tension zone in the stress distribution pattern.